2014
DOI: 10.5713/ajas.2013.13448
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling Characteristics and the <italic>In situ</italic> Nutrient Degradability of a By-product Feed-based Silage

Abstract: This study was conducted to evaluate the ensiling characteristics and the in situ degradability of a by-product feed (BF)-based silage. Before ensilation, the BF-based mixture was composed of 50% spent mushroom substrate, 21% recycled poultry bedding, 15% ryegrass straw, 10.8% rice bran, 2% molasses, 0.6% bentonite, and 0.6% microbial inoculant on a wet basis and ensiled for up to 4 weeks. The BF-based silage contained on average 39.3% moisture, 13.4% crude protein (CP), and 52.2% neutral detergent fiber (NDF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In addition, previous studies showed that Lactobacillus spp. inoculated into SMS can improve fermentation, preservation and digestibility of SMS (Muck et al, 2007;Kim et al, 2014). However, to the best of our knowledge, no study has examined the efficacy of LAB inoculation into SMS on ruminal fermentation and digestibility in Korean native Hanwoo cattle.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, previous studies showed that Lactobacillus spp. inoculated into SMS can improve fermentation, preservation and digestibility of SMS (Muck et al, 2007;Kim et al, 2014). However, to the best of our knowledge, no study has examined the efficacy of LAB inoculation into SMS on ruminal fermentation and digestibility in Korean native Hanwoo cattle.…”
Section: Introductionmentioning
confidence: 98%
“…et al (2007) reported that LAB inoculation seemed to affect in vitro ruminal fermentation characteristics. Kim et al (2014) (Muck et al, 2007;Kim et al 2014) was different from LAB used in our study. The use of different LAB inoculants may lead to different results in ruminal fermentation characteristics.…”
Section: Nutrients Digestibility Of Smsp and Ismsp Diets In Hanwoo Stmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study [6], cheap and high quality BF-based roughage was successfully manufactured by ensiling spent mushroom substrate (SMS), recycled poultry bedding (RPB), rice bran, minimal straw with added molasses, and highly cellulolytic microbes, which were isolated from the SMS [7]. The silage exhibited favorable ensiling characteristics as well as higher degradability of dry matter (DM) and crude protein (CP) compared to RS or ryegrass straw [6].…”
Section: Introductionmentioning
confidence: 99%
“…최근에 부산물사료(버섯재배부산물, 재활용양계깔개, 미 강 등)를 주원료로 하여 양질의 발효부산물 조사료 제조에 대한 연구가 행하여졌다 (Kim et al, 2014). 이의 주원료의 하나로 이용되는 고섬유성 버섯재배부산물(spent mushroom substrate, SMS)은 년간 약 97만 톤이 발생되며, 이를 이용 해 SMS 주원료의 사일리지를 제조하면 연간 약 194만 톤 의 부산물 조사료 생산이 가능하다고 하였다 (Kim, 2007).…”
unclassified